The ableist Othering of disability in the classroom: an experiential investigation of academic adjustments in higher education - Reutlinger, Corey Jon (Kansas State University, 2015)
Due to a rising interest for degrees in higher education, more students with disabilities have enrolled in the university system. Still, accessibility issues on campuses suggest institutions are not meeting the needs of students in the classroom or through curricula. This study examines current academic adjustments and the lived experiences of students with disabilities in order to understand the ableist Othering phenomenon in higher education. Qualitative research methods have been commonly used to investigate the “disabled voice”; however, triangulation of such methodologies has been criticized for reinforcing Otherness. This study used a phenomenological design implementing rhetorical agency for disabled students to answer open-ended questions in semi-structured interviews about their lived experiences. Consequently, such interviews created a platform for social change. The author also reflects on his own lived experiences as a deaf student in higher education. Findings include major themes such as a percolation of institutional hegemony, a re-appropriation of stigma through “voice,” and a call for inclusive strategies. Results indicate disabled students experience discrimination likely due to organizational tension in their university institution. Further, this study elaborates on proposed policy changes to college classrooms on large university campuses. Contributions of this study lie in implications for the future of qualitative inquiry, including how current research practices could undergo methodological reinvention to examine the ableist Othering phenomenon.
Keywords: accessibility; disability; triangulation; ableist Othering; rhetorical agency; Communication (0459); Special Education (0529); Theoretical Mathematics (0642)